Dietary protein intake is not associated with 5-y change in mid-thigh muscle cross-sectional area by computed tomography in older adults: the Health, Aging, and Body Composition (Health ABC) Study. Issue 3 (8th March 2019) - Verreijen, Amely M; Engberink, Mariëlle F; Houston, Denise K; Brouwer, Ingeborg A; Cawthon, Peggy M; Newman, Ann B; Tylavsky, Frances A; Harris, Tamara B; Weijs, Peter J M; Visser, Marjolein
ABSTRACT: Background: A higher protein intake is suggested to preserve muscle mass during aging and may therefore reduce the risk of sarcopenia. Objectives: We explored whether the amount and type (animal or vegetable) of protein intake were associated with 5-y change in mid-thigh muscle cross-sectional area (CSA) in older adults ( n  = 1561). Methods: Protein intake was assessed at year 2 by a Block food-frequency questionnaire in participants (aged 70–79 y) of the Health, Aging, and Body Composition (Health ABC) Study, a prospective cohort study. At year 1 and year 6 mid-thigh muscle CSA in square centimeters was measured by computed tomography. Multiple linear regression analysis was used to examine the association between energy-adjusted protein residuals in grams per day (total, animal, and vegetable protein) and muscle CSA at year 6, adjusted for muscle CSA at year 1 and potential confounders including prevalent health conditions, physical activity, and 5-y change in fat mass. Results: Mean (95% CI) protein intake was 0.90 (0.88, 0.92) g · kg –1 · d –1 and mean (95% CI) 5-y change in muscle CSA was −9.8 (−10.6, −8.9) cm 2 . No association was observed between energy-adjusted total (β = −0.00; 95% CI: −0.06, 0.06 cm 2 ; P  = 0.982), animal (β = −0.00; 95% CI: −0.06, 0.05 cm 2 ; P  = 0.923), or plant (β = +0.07; 95% CI: −0.06, 0.21 cm 2 ; P  = 0.276) protein intake and muscle CSA at year 6, adjusted for baseline mid-thigh muscle CSA and potential confounders. Conclusions: This study suggests that a higher total, animal, or vegetable protein intake is not associated with 5-y change in mid-thigh muscle CSA in older adults. This conclusion contradicts some, but not all, previous research. This trial was registered at www.trialregister.nl as NTR6930.